Bilateral agreement for the academic year 2011-2012-2012/13 LLP Programme: Higher Education Erasmus between Universidade Lusíada de Lisboa and Universitat Autònoma de Barcelona - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the LLP programme (Erasmus); - Subject area: Tourism, catering, hotel management.